2023
DOI: 10.3389/fgeed.2023.1078359
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 mediated gene editing in non-model nematode Panagrolaimus sp. PS1159

Abstract: The phylum Nematoda harbors a huge diversity of species in a broad range of ecosystems and habitats. Nematodes share a largely conserved Bauplan but major differences have been found in early developmental processes. The development of the nematode model organism Caenorhabditis elegans has been studied in great detail for decades. These efforts have provided the community with a large number of protocols and methods. Unfortunately, many of these tools are not easily applicable in non-Caenorhabditis nematodes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…To seek for a dominant allele that produces a consistent and visible phenotype as a co-CRISPR marker, I targeted Sh-unc-22, predicted to encode a muscle gene termed Twitchin protein in free-living and parasitic nematodes (Gang et al, 2017; Hellekes et al, 2023; Moerman et al, 1988). In nematodes, UNC-22 is crucial in maintaining muscle contraction cycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To seek for a dominant allele that produces a consistent and visible phenotype as a co-CRISPR marker, I targeted Sh-unc-22, predicted to encode a muscle gene termed Twitchin protein in free-living and parasitic nematodes (Gang et al, 2017; Hellekes et al, 2023; Moerman et al, 1988). In nematodes, UNC-22 is crucial in maintaining muscle contraction cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The CRISPR-Cas9 system has been successfully adopted in various nematode species, including the classical model C. elegans, the necromenic nematode Pristionchus pacificus, the mammalian parasite Strongyloides stercoralis, and other non-model species, such as Aunema , Oscheius, and Panagrolaimus (Adams et al, 2019; Castelletto & Hallem, 2021; Dockendorff et al, 2022; Hellekes et al, 2023; Hiraga et al, 2021; H.-M. Kim et al, 2022; Lok, 2019). In these successful cases, either plasmid encoded Cas9 and guide RNAs or Cas9 RNP were delivered through microinjection into the gonad of a hermaphrodite or a female nematode.…”
Section: Introductionmentioning
confidence: 99%
“…Further research regarding nematode Hox gene complements that we have identified in the present study should seek to understand whether and where the colinear expression is retained in the phylum. As more species become amenable to molecular methods 48,51,72 , this can be done with tools like in situ hybridization, single-cell RNA-Seq studies, and CRISPR-guided gene knockouts. In summary, our analyses suggest the potential for new and exciting work on Hox genes and regulation of Hox clusters in a broad sampling of Nematoda.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting alleles were consistent with a mixture of NHEJ and MMEJ double-strand break repair (Xue and Greene 2021); we saw no evidence of homology-directed repair using the oligonucleotide template we had included. CRISPR-Cas9 is used extensively in established laboratory research animals and is emerging as a powerful tool in a growing variety of nematodes that have not previously been used extensively in laboratory research (Mendez et al 2022;Cadd et al 2022;Hellekes et al 2023;Dutta et al 2023); it is only with our work and with recent work from Mengyi Cao (personal communication) that CRISPR-Cas9 has been extended to entomopathogenic nematodes. We wish to particularly highlight the potential utility of the skpo-2 locus in performing CRISPR studies using other Steinernema entomopathogens.…”
Section: Prospects For Crispr-cas9 Gene Targeting In Steinernemamentioning
confidence: 99%